Glutamate 73 Promotes Anti-arrhythmic Effects of Voltage-Dependent Anion Channel Through Regulation of Mitochondrial Ca2+ Uptake - Shimizu, Hirohito; Huber, Simon; Langenbacher, Adam D.; Crisman, Lauren; Huang, Jie; Wang, Kevin; Wilting, Fabiola; Gudermann, Thomas; Schredelseker, Johann; Chen, Jau-Nian (Frontiers in Physiology, 2021)
Mitochondria critically regulate a range of cellular processes including bioenergetics, cellular metabolism, apoptosis, and cellular Ca2+ signaling. The voltage-dependent anion channel (VDAC) functions as a passageway for the exchange of ions, including Ca2+, across the outer mitochondrial membrane. In cardiomyocytes, genetic or pharmacological activation of isoform 2 of VDAC (VDAC2) effectively potentiates mitochondrial Ca2+ uptake and suppresses Ca2+ overload-induced arrhythmogenic events. However, molecular mechanisms by which VDAC2 controls mitochondrial Ca2+ transport and thereby influences cardiac rhythmicity remain elusive. Vertebrates express three highly homologous VDAC isoforms. Here, we used the zebrafish tremblor/ncx1h mutant to dissect the isoform-specific roles of VDAC proteins in Ca2+ handling. We found that overexpression of VDAC1 or VDAC2, but not VDAC3, suppresses the fibrillation-like phenotype in zebrafish tremblor/ncx1h mutants. A chimeric approach showed that moieties in the N-terminal half of VDAC are responsible for their divergent functions in cardiac biology. Phylogenetic analysis further revealed that a glutamate at position 73, which was previously described to be an important regulator of VDAC function, is sevolutionarily conserved in VDAC1 and VDAC2, whereas a glutamine occupies position 73 (Q73) of VDAC3. To investigate whether E73/Q73 determines VDAC isoform-specific anti-arrhythmic effect, we mutated E73 to Q in VDAC2 (VDAC2E73Q) and Q73 to E in VDAC3 (VDAC3Q73E). Interestingly, VDAC2E73Q failed to restore rhythmic cardiac contractions in ncx1 deficient hearts, while the Q73E conversion induced a gain of function in VDAC3. In HL-1 cardiomyocytes, VDAC2 knockdown diminished the transfer of Ca2+ from the SR into mitochondria and overexpression of VDAC2 or VDAC3Q73E restored SR-mitochondrial Ca2+ transfer in VDAC2 deficient HL-1 cells, whereas this rescue effect was absent for VDAC3 and drastically compromised for VDAC2E73Q. Collectively, our findings demonstrate a critical role for the evolutionary conserved E73 in determining the anti-arrhythmic effect of VDAC isoforms through modulating Ca2+ cross-talk between the SR and mitochondria in cardiomyocytes.